Ordering-mediated local nano-clustering results in unusually large Hall-Petch strengthening coefficients in high entropy alloys. Issue 5 (4th May 2021) - Jagetia, A.; Nartu, M.S.K.K.Y.; Dasari, S.; Sharma, A.; Gwalani, B.; Banerjee, R.
Abstract : This paper reports a dramatic increase in the grain boundary strengthening or Hall-Petch coefficient, K, by systematically investigating the effect of Al addition on tensile yield strength in CoFeNi and CoCrFeNi high entropy alloys (HEAs) or complex concentrated alloys (CCAs). Additionally, detailed atom probe tomography (APT) revealed a high number density of Ni-Al rich nano-clusters in the Al0.3 CoFeNi and Al0.3 CoCrFeNi HEAs/CCAs, which can be rationalized based on the strong chemical ordering tendency between these elements. Consequently, the huge increase in K value can be attributed to the additional stress required for overcoming coherency strain fields arising from these nano-clusters. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: This paper reports that the Hall-Petch co-efficient (K) dramatically increase when Al is added to CoFeNi/CoCrFeNi alloys. Such a trend is attributed to the ordering mediated nano-clustering in Al containing HEA/CCAs.